Intermolecular ionic cross-linked sulfonated poly(ether ether ketone) membranes with excellent mechanical properties and selectivity for direct methanol fuel cells. Issue 27 (29th February 2016) - Li, Guibin; Zhao, Chengji; Cui, Ying; Rong, Tao; Zhu, Chongyi; Na, Hui
Abstract : The composite membranes based on APEEK and SPEEK with good proton conductivity, excellent mechanical and thermal stabilities were prepared successfully. Abstract : Amino-substituted poly(ether ether ketone) (APEEK) and sulfonated poly(ether ether ketone) (SPEEK, IEC = 2.07 mequiv. g −1 ) have been synthesized via nucleophilic aromatic substitution reaction. The structures of APEEK and SPEEK were characterized by 1 H NMR spectra. The composite membranes based on APEEK and SPEEK were confirmed by their FTIR spectra, indicating the formation of intermolecular ionic cross-linking networks between amino and sulfonic groups. The water uptake, proton and methanol transport properties of composite membranes were also determined for fuel cell applications. The results showed that the composite membranes exhibit high selectivity, appropriate proton conductivities as well as reduced water uptake and methanol permeability when compared with the pristine SPEEK membrane. Furthermore, it should be noted that the intermolecular ionic cross-linking effectively improved the tensile strength, breaking elongation, and thermal stabilities of the membranes. In particular, the SPEEK-10 membrane (the weight ratio of APEEK is 10%) showed a tensile strength of 121.2 MPa and breaking elongation of 93.5%, which were 1.5 times and 2.5 times higher than those of pristine SPEEK, respectively. The high selectivity, thermal and mechanical properties indicate that the composite membranes are promising to be used as proton exchange membranes for direct methanol fuel cells.